A Theoretical Review of the Literature: Domestic Violence in Muslim Communities in the United States - Ahmed, Rashid; Gupta, Prita; Saeed, Sadia; Jayasundara, Dheeshana; Nedegaard, Randall (Journal of Social Work Education and Practice, 2019)
Social workers are often tasked to engage with families where domestic violence is occurring. This challenging task can be exacerbated by factors such as cultural and religious influences. As a means to increase the understanding of these important factors, an extensive literature review of current material on Islam, Muslims and domestic violence was conducted. This literature was divided into several themes to include: Islam and Muslims; Islam, marriage and family; Islam and domestic violence; special circumstances of Muslim victims of domestic violence; why Muslim women stay; the September 11th impact on domestic violence in Muslim families in the US; and services available to these families. Implications include increased knowledge acquisition and cultural awareness as well as a call for more knowledge regarding the relationship between the intersections of factors such as Islam, culture, immigration and socioeconomic status, and the competent assessment of service needs and successful service delivery.